Lingkungan Sosial dengan Perilaku Seksual Berisiko pada Remaja - Maryam Rauf; Vivien Novarina A. Kasim; Nirwanto K. Rahim (Journal of Telenursing (JOTING), 2026)
This study aims to analyze the relationship between the social environment and risky sexual behavior in adolescents. The method used was a quantitative approach with a cross-sectional design and bivariate analysis using the Spearman's rho test. The results showed a p-value of 0.198 (>0.05) with a correlation coefficient of -0.126. In conclusion, there is no significant relationship between the social environment and risky sexual behavior in adolescents at SMP Negeri 15 Gorontalo. The direction of the negative relationship indicates that the better the social environment, the lower the tendency for risky sexual behavior. However, this relationship is very weak and not statistically significant. Keywords: Social Environment, Risky Sexual Behavior, Adolescents